Pengaruh Model Problem Based Learning Terhadap Minat Belajar Siswa dan Kemampuan Berkolaborasi di Pembelajaran IPA UPT SMP Negeri 6 Tambang - Era Festivalia (Journal of Innovation in Teaching and Instructional Media, 2026)
Science learning in junior high schools still faces the problem of low student interest in learning and collaboration skills due to the dominance of teacher-centered learning. This study aims to determine the effect of implementing the Problem-Based Learning (PBL) model on students' interest in learning and collaboration skills in ninth-grade science at the UPT SMP Negeri 6 Tambang. The study used a quantitative approach with a quasi-experimental model and a nonequivalent control group design. The study sample consisted of two classes: an experimental class implementing the PBL model and a control class using conventional learning. Data collection techniques included a learning interest questionnaire, observations of collaboration skills, an assessment rubric, and documentation. Data analysis was conducted using descriptive and inferential statistics with a t-test. The results showed a significant difference between the experimental and control classes, with students' interest in learning and collaboration skills being higher in the experimental class. It can be concluded that the Problem-Based Learning model has a positive and significant effect on increasing students' interest in learning and collaboration skills in science learning.